Spiritual Intelligence and Resilience Among Volunteers: A Study of Disaster Volunteers at Indonesian Red Cross Society (PMI) in Bandar Lampung - Salwa Chania; Chania, Salwa; Khairani (Universitas Islam Negeri Raden Intan Lampung, 2025)
Volunteers frequently experience high levels of psychological pressure while serving in disaster zones, which may lead to stress and trauma due to demanding working conditions. Resilience is essential in helping volunteers remain strong and adaptive, while spiritual intelligence is believed to enhance life meaning and foster positive attitudes when facing adversity. This study aimed to examine the relationship between spiritual intelligence and resilience among disaster volunteers at Indonesian Red Cross Society (PMI) in Bandar Lampung. A quantitative correlational approach was employed, involving 73 participants selected through purposive sampling. Data were collected using the Spiritual Intelligence Self-Report Inventory (SISRI-24) and the Connor–Davidson Resilience Scale (CD-RISC). Pearson’s Product-Moment correlation analysis revealed a positive and statistically significant relationship between spiritual intelligence and resilience (r = 0.705, p = 0.000, p < 0.05). Furthermore, the Conscious State Expansion dimension of spiritual intelligence demonstrated the strongest correlation with resilience. These findings indicate that volunteers with higher levels of spiritual intelligence tend to exhibit greater resilience, enabling them to manage stress effectively, adapt to change, and recover from challenging experiences in disaster settings. This study highlights the importance of spiritual intelligence as a key internal factor that supports volunteer resilience in carrying out humanitarian responsibilities. Keywords: disaster, spiritual intelligence, volunteers, resilience, stress